The Recording Industry's Influence on Vernacular Traditions 1920-1960: Illustrated Case Studies of Mamie Smith, the Carter Family, and Leadbelly - (:unkn) unknown (My University, 2013)
In this study, the Kingston Trio's 1958 recording of "Tom Dooley" is used as a starting point to explore the recording industry's commercialization of folk music in the first half of the twentieth century. Three case studies - Mamie Smith, the Carter Family, and Leadbelly - address trends in academic folk music scholarship that juxtaposed an initial rise in a commercial music culture that began with early 1920s race recordings and culminates in the folk-revival in the post-WWII period. These trends trace back into the nineteenth century, and include African American performance traditions that were incorporated into pre-civil war minstrelsy and late century vaudeville, and include African American theater, ragtime, "coon singing," and popular blues. This discussion highlights times in the early 1920s, the late 1920s, and the early 1930s, that were crucial to changing the sound and performance practice of traditional folk and vernacular traditions into more commercial products. This thesis culminates in a discussion of the direction taken by folk music in the early 1960s with the appearance of commercial groups associated with the folk revival movement and the emergence of folk rock.
Keywords: Folk; Minstrelsy; Recording; Tom Dooley; Vaudeville; Vernacular